Hubungan islam dan barat: Benturan atau kerjasama - Dewi, Trisia Megawati Kusuma (Institute for Advanced Science, Social, and Sustainable Future, 2024)
The Saudi Arabia-Iran reconciliation initiated by China has implications for the role of the United States (US) in the conflict. Saudi Arabia is beginning to see China as a rising power, while the U.S. is facing geopolitical shifts in the Middle East. The economic proximity between Saudi Arabia and China reduces Saudi Arabia's dependence on the US. The US should acknowledge the changing power dynamics and consider China's position in its policy regarding the Saudi Arabia-Iran conflict. This reconciliation requires the US to adapt to geopolitical power shifts and face new challenges in the region. Meanwhile, Saudi Arabia began to focus on revamping priority aspects with the shift of oil energy as a mainstay to green energy with the implementation of Vision 2030.